Development of aerobic granules for enhanced biological wastewater treatment - Jiang, Helong (2008)
To investigate the ability of aerobic granules to efficiently degrade toxic and inhibitory substrates, a column-type SBR was operated with phenol as the sole carbon source at a rate of 1.5 g phenol 1-1 day-1. Aerobic granules first appeared on day 9 of reactor operation and quickly grew to displace the seed flocs as the dominant form of biomass in the reactor. These granules were compact in appearance, had a mean size of 0.52 mm and a sludge volume index of 40 ml g-1 SS. The compact structure of aerobic granules offers several advantages, namely easy separation of biomass from bulk liquid during settling phase, high biomass retention, and protection of cells against the effects of phenol toxicity. Compared to conventional activated sludge systems and SBR with flocculated sludge, phenoldegrading aerobic granules can be exploited to design compact, high-rate aerobic granulation systems for the treatment of industrial wastewaters containing high concentrations of phenol and other inhibitory chemicals.